2022
DOI: 10.3390/ijms23158497
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Aberrant Long Non-Coding RNA-Mediated Competitive Endogenous RNA Network and Alzheimer’s Disease Pathogenesis

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disorder characterized by cognitive dysfunction. The role of long non-coding RNAs (lncRNAs) with the action of competitive endogenous RNA (ceRNA) in AD remains unclear. The present study aimed to identify significantly differentially expressed lncRNAs (SDELs) and establish lncRNA-associated ceRNA networks via RNA sequencing analysis and a quantitative real-time Polymerase Chain Reaction (qPCR) assay using transgenic mice with five familial AD mutations. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The Morris water maze (MWM) test was used to evaluate the impairment of spatial learning and memory of 5 × FAD mice ( Liu et al, 2018 ; Jiang et al, 2022 ; Sun et al, 2022 ). A different cohort from the Cai et al (2022) study was used for MWM test. Briefly, The testing included place navigation training and space memory trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Morris water maze (MWM) test was used to evaluate the impairment of spatial learning and memory of 5 × FAD mice ( Liu et al, 2018 ; Jiang et al, 2022 ; Sun et al, 2022 ). A different cohort from the Cai et al (2022) study was used for MWM test. Briefly, The testing included place navigation training and space memory trials.…”
Section: Methodsmentioning
confidence: 99%
“…The total RNA of the hippocampus was isolated with TRIzol reagent (Invitrogen, CA, United States) according to the previous protocol ( Zhao et al, 2022 ). The RNA sample used in this study was the same cohort as our reported investigation ( Cai et al, 2022 ). Subsequently, the RNA integrity was determined using gel electrophoresis ( Supplementary Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ceRNA hypothesis proposes that RNA transcripts, both coding and noncoding, crosstalk with and regulate each other via microRNA response elements (Thomson and Dinger, 2016). The ceRNA hypothesis suggests that the regulatory interactions between different RNA types are important for the development, progression, and regulation of various diseases, including cancer, cardiovascular diseases, and neurological disorders (Cai et al, 2022;Liang et al, 2020;. Furthermore, increasing evidence suggests that ceRNAs play a vital role in reproductive health, including fetal development, preeclampsia, gestational diabetes, and spontaneous abortion (Gan et al, 2022;Jain et al, 2022;Leng et al, 2019;S.…”
Section: Cerna Regulatory Network In Icpmentioning
confidence: 99%
“…Excessive mitochondrial fission promotes mitophagy through the PTEN-induced kinase 1 (PINK1)/Parkin-mediated mitophagy pathway, with a convergence of the miR-351-5p/MIRO2 axis in the pathology of AD (Chen et al, 2016). With the ongoing development of high-throughput sequencing and microarray technologies, many novel ncRNAs with regulatory roles in NDs are being identified (Cai et al, 2022b;Sun et al, 2022b;Zhao et al, 2022). For example, miR-455-3p is a newly discovered miRNA that showed significant upregulation in AD (Kumar et al, 2017), and its overexpression positively regulated the expression of mitochondrial biogenesis genes.…”
Section: Ncrnas Regulate Mitochondrial Gene Expressionmentioning
confidence: 99%